Cadential Rhetoric and Separate Agencies: Split-Voice PACs and their Impact on Formal Closure in the Music of Dvořák - Xieyi (Abby) Zhang (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2025)
This article analyzes three pieces by Dvořák that make use of a cadential device henceforth referred to as a split PAC: either the melody or the bass appears to cadence significantly before the other—often by several measures—and maintains a holding pattern until the other voice catches up. This paper begins by contextualizing split PACs within the existing formal theory of cadences. Then, using the analytical perspective of multiple agencies, this paper reads these cadential gestures as drivers of musical narrative that often have long-lasting implications for the remainder of the piece.
Keywords: nineteenth-century music; form; multiple agency; cadence; Dvořák